Мотивы включения студентов Софийского университета в волонтерские деятельности - Yaneva, Anzhelina; Prokopov , Emil (Student Niepełnosprawny. Szkice i Rozprawy, 2019)
The paper explores the motives of students included and not included in volunteer activities. An online anonymous survey was conducted among sports students at Sofia Uni-versity, with questions allowing open and closed answers. The article presents students' atti-tudes and motivations to engage in volunteer activities. The results of the survey highlight the issues that need to be addressed to sportspeople, changing their attitudes towards sports and volunteer activities in sports.